Vida esterilizada: reflexões biopolíticas sobre as estratégias de comercialização de sêmen no Banco California Cryobank - Mazzilli, Paola (2017)
The present work aimed at investigating and problematizing the global human sperm bank market, at the beginning of the 21st century. In view of the significant increase in sperm imports in Brazil (2,625% between 2011 and 2016) and the interest in premium donor catalogs, we carried out an exploratory study that could unravel its offer. Our purpose was to understand how the advertising strategies of this market would promote the expectation of a child ‘customization’, from the possibility of selecting an ‘ideal’ biological father. In addition, we deem it necessary to reflect on the new meanings attributed to motherhood, fatherhood and birth itself, considering progresses in the fields of biotechnology and genetics. To do so, we collected current data on the fertility market, paying special attention to the national and international commercialization of sperm. We also addressed the ‘parallel market’, where ‘independent’ donors provide their services in a paid or free basis. Finally, we conducted a case study of California Cryobank, one of the most important banks in the world. In order to understand its business dynamics, we decided to discuss it in two stages: the first one was devoted to its services offer and the second one to the catalog of its donors, which was statistically and discursively analyzed in its entirety (533 ads). We then identified what would be the main attributes that, a priori, would characterize these ‘premium’ donors. From the theoretical point of view, we preferred a transversal approach with special emphasis on contemporary authors dealing with biopower and biotechnology. We hope that the research developed may contribute to new debates, in that it articulates, in an unprecedented and representative way, empirical data and academic reflections